"Breathing the Air of a World So New": Rewriting the Landscape of America in Toni Morrison's A Mercy. (February 2014) - TERRY, JENNIFER
<x content-type="archive" xml:space="preserve">Abstract</x> This article explores Toni Morrison's preoccupation with, and reimagining of, the landscape of the so-called New World. Drawing on scholarship that has investigated dominant discourses about freedom, bounty, and possibility located within the Americas, it identifies various counternarratives in Morrison's fiction, tracing these through the earlier Song of Solomon (1977), Tar Baby (1981), and Beloved (1987), but primarily arguing for their centrality to A Mercy (2008). The mapping of seventeenth-century North America in the author's ninth novel both exposes colonial relations to place and probes African American experiences of the natural world. In particular, A Mercy is found to recalibrate definitions of "wilderness" with a sharpened sensitivity to the position of women and the racially othered within them. The dynamic between the perspectives towards the environment of Anglo-Dutch farmer and trader Jacob Vaark and Native American orphan and servant Lina, is examined, as well as the slave girl Florens's formative encounters in American space. Bringing together diverse narrative views, A Mercy is shown to trouble hegemonic settler and masculinist notions of the New World and, especially through Florens's voicing, shape an alternative engagement with landscape. The article goes some way towards meeting recent calls for attention to the intersections between postcolonial approaches and ecocriticism.